Public Debt and Economic Growth in The SouthEast Asian Countries - Muhammad Ghafur Wibowo (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2017)
This study examines the relationship between public debt and economic growth in eight countries in Southeast Asia that are members of ASEAN. Through the study will contribute reference for each country to establish their macroeconomic policies. Using 10 years of data from 2006 to 2015 and analysis tools Autoregression Vector (VAR), the study attempts to test the theory of finance led growth. The main finding of this study is that public debt is actually able to increase the economic growth of a country significantly, although it takes a few years of its existence. This finding supports several previous studies that demonstrate the important role of government debt to the economy of a country.DOI: 10.15408/sjie.v6i1.4779